PERLINDUNGAN HUKUM OLEH PEMERINTAH KOTA SAMARINDA BAGI PENYANDANG DISABILITAS SEBAGAI PEJALAN KAKI - Andayani, Ana; Muslim, Ikhwanul (Jurnal Riset Inossa : Media Hasil Riset Pemerintahan, Ekonomi dan Sumber Daya Alam, 2023)
Law Number 22 of 2009, concerning Road Traffic and Transportation, states that "pedestrians are people who walk in the traffic room". So, what is meant by walking is not only those who can walk normally but those with the status of persons with disabilities, including those who use walking aids. Therefore, to realize the equality of rights for persons with disabilities in utilizing pedestrian facilities such as sidewalks, it is also necessary to have special protection carried out by the government, both central and local governments. One of the legal protections that can be done is to provide legal certainty to the rights owned by forming a statutory regulation. With a juridical normative research method, the author conducted research by observing legal documents related to the title of this research. The results of this study found that there were documents as a form of legal protection for the Samarinda City government as a form of protection for pedestrians with disabilities, namely the Samarinda City Regulation Number 11 of 2017 concerning Protection and Fulfillment of the Rights of Persons with Disabilities, Cooperation Agreements by the Disdukcapil of Samarinda City with PPDI City. Samarinda, Road Decree by the Samarinda City PUPR Office regarding the Samarinda City road section, as well as the existence of a plan drawing document for pavement construction accompanied by the accessibility for persons with disabilities by the Samarinda City PUPR Office.